Long non‐coding PANDAR as a novel biomarker in human cancer: A systematic review. (10th December 2017) - Zou, Yifan; Zhong, Yuantang; Wu, Junjie; Xiao, Huizhong; Zhang, Xintao; Liao, Xinhui; Li, Jianfa; Mao, Xuhua; Liu, Yuchen; Zhang, Fuyou
Abstract: Objectives: Long non‐coding RNAs (lncRNAs) are characterized as a group of RNAs that more than 200 nucleotides in length and have no protein‐coding function. More and more evidences provided that lncRNAs serve as key molecules in the development of cancer. Deregulation of lncRNAs functions as either oncogenes or tumour suppressor genes in various diseases. Recently, increasing studies about PANDAR in cancer progression were reported. In our review, we will focus on the current research on the character of PANDAR include the clinical management, tumour progression and molecular mechanisms in human cancers. Materials and methods: We summarize and analyze current studies concerning the biological functions and mechanisms of lncRNA PANDA in tumour development. The related studies were obtained through a systematic search of Pubmed. Results: PANDAR was a well‐characterized oncogenic lncRNA and widely overexpressed in many tumours. PANDAR is upregulated in many types of cancer, including colorectal cancer, lung cancer, renal cell carcinoma, cholangiocarcinoma, osteosarcoma, thyroid cancer and other cancers. Upregulation of PANDAR was significantly associated with advanced tumour weights, TNM stage and overall survival. Furthermore, repressed of PANDAR would restrain proliferation, migration and invasion. Conclusion: PANDAR may act as a powerful tumour biomarker for cancer diagnosis and treatment.